Creative tourism as boosting tool for placemaking strategies in peripheral areas: insights from Portugal - Gato, M. A. (2021)
Creative tourism is starting in Portugal as a labelled and structured alternative aiming to produce a boosting effect in peripheral areas. By linking places, host communities and tourists in the cocreation of differentiated experiences, this tourism offer challenges destinations and communities to be creative and reinvent themselves as placemaking agents in the coproduction of territorial amenities. As such, creative tourism can be a useful tool to complement placemaking strategies in peripheral areas, once it has the ability to engage local communities and generate territorial benefits. This hypothesis is explored through a case study and preliminary findings, obtained through focus group, in-depth interviews and content analysis, show the advantages of planned placemaking strategies for the territorial promotion. The comparisons in terms of intervention focus by types of entities and placemaking strategies confirm the complexity of these dynamics, pointing relevant factors used to mobilize local tangible and intangible resources.